Gender Equality in Climate Change Adaptation: A Case of Cirebon, Indonesia - Nila Ardhyarini H. Pratiwi; Yovi Dzulhijjah Rahmawati; Ivo Setiono (The Indonesian Journal of Planning and Development, 2017)
Climate change will greatly affect many aspects of Indonesia’s economy, society, and environment. The vulnerability of individuals to climate change will depend on their adaptive capacity and manifestations of gender inequality can affect this capacity. It is generally acknowledged that women may be more vulnerable to climate change impact than men. Therefore, gender inequality becomes the critical issue on climate change adaptation. However, it is not yet mainstreamed into climate change adaptation program in Indonesian cities. With regard to such circumstance, this study assessed the gender dimensions in the context of climate change vulnerability, and how to mainstream gender-sensitive into climate change adaptation program at the local level with a case of Cirebon, Indonesia, in urban and rural areas. Mixed methods were employed for this study by combining quantitative and qualitative analysis through explanatory and comprehensive analysis. We examined the gender differences on socio-economic condition by using the socio-ecological model with various variables consisting of literacy and education, livelihood, access to and control over resources, health, mobility, female-headed household, and roles in decision-making. The results highlight that there are different gender’s adaptive capacities between urban and rural areas to climate change, and gender mainstreaming in climate change adaptation in an urban area is easier to be implemented than in a rural area which influenced by the level of society and policymakers ability and awareness.